Pengaruh Motivasi Kerja, Gaya Kepemimpinan Dan Kompetensi Terhadap Kepuasan Kerja Pegawai Pada Organisasi Pemerintahan - Rahmat Hidayat, Rahmat (Politeknik Pelayaran Sulawesi Utara, 2021)
RAHMAT HIDAYAT. 2021. The Effect of Motivation, Leadership Style and Competence on Employee Satisfaction in Government Organizations. These research aim to anlaysis the effect motivation, leadership style and competence toward satisfaction by employee and analysis the dominant effect between the researched variable toward satisfaction in Government Organizations. This type of research is quantitative designed to answer the problem that have been formulated and the objectives to be achieved and test the hypothesis. Population of research namely all of employee from 115 Organization Job United Organization as amount 5.991 orang. The sample size was chosen using the Slovin formulation obtained as amount 98 responden. Data analysis used descriptive analysis and multiple linier regression analysis. The result of the study found that motivation have positive and significant effect toward satisfaction by employee. These meaning the motivation have applied consist of actualization, esteem, cooperation, communicated and feature compensation, so affected toward satisfaction it. The leadership style have positive and significant toward satisfaction by employee. The leadership style such as instruction, consultation, participative and delegation have applied and get satisfaction by employee. The competence have effected and significant toward satisfaction. The actualization of competence suitable with the knowledge, skill, experience and attitude have get the satisfaction by employee in activities. The competence have dominan effect that meaning the competence get contribution toward satisfaction based of the routine of job, accepted of challenge, have prestation and creative and satisfied with the job promotion.